Why should we share our data, how can it be organized, and what are the challenges ahead? - Denis Huschka (Rat für Sozial- und Wirtschaftsdaten (RatSWD), 2013)
The paper is based on a keynote talk held at the international conference Opening data services in the social sciences, Belgrade, Serbia, 20/21 March 2013. The author wishes to thank the SERSCIDA project. Empirical social sciences strongly contribute towards a better understanding of societies, especially of those societies that undergo rapid social changes. Empirical analyses are fed into the steering processes that are shaping a Europe of Nations. But data are also essential for the support of social and economic developments in national contexts. I was asked to reflect on three questions in my talk, namely: Why should we share our data? How can data sharing be organized? And what are the challenges ahead?
Keywords: 330